Effectiveness of Clinical Pharmacy Interventions in Medication Adherence for Geriatric Patients: Literature Review - Ilham, Febrian Dzikri; Hilmi, Indah Laily; Sudarjat, Hadi (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2025)
Background: Medication adherence in geriatric patients is a major challenge as polypharmacy increases the risk of drug-related problems (DRPs). The role of clinical pharmacy is important in addressing these issues through evidence-based approaches. Objective: To review the effectiveness of various clinical pharmacy interventions in improving medication adherence in geriatric patients. Methods: This article used a systematic review of 13 literature selected from 934 articles based on inclusion criteria in the last 10 years, using PubMed and Google Scholar databases. The focus of the analysis included education, monitoring, and the use of tools such as pill cards and medication reminder charts. Results: Clinical pharmacy interventions, such as the use of Beers and STOPP/START criteria, counseling, and educational programs using tools, were shown to improve adherence in geriatric patients. Programs such as pill boxes increased adherence by 83.33%. However, some tools such as medication reminder charts had limited effectiveness. Conclusion: A collaborative approach, including patient and family education, monitoring, and clinical criteria-based therapy adjustments, is essential to improve medication adherence in geriatric patients, which directly improves their quality of life.